Periprosthetic Infection Due to Resistant Staphylococci: Serious Problems on the Horizon - Parvizi, Javad (Springer-Verlag, 2009)
Prosthetic joint infections (PJI) caused by methicillin-resistant staphylococci represent a major therapeutic challenge. We examined the effectiveness of surgical treatment in treating infection of total hip or knee arthroplasty caused by methicillin-resistant staphylococcal strains and the variables influencing treatment success. One hundred and twenty-seven patients were treated at our institution between 1999 and 2006. There were 58 men and 69 women, with an average age of 66 years. Patients were followed for a minimum of 2 years or until recurrence of infection. Débridement and retention of the prosthesis was performed in 35 patients and resection arthroplasty in 92. Débridement controlled the infection in only 37% of cases whereas two-stage exchange arthroplasty controlled the infection in 75% of hips and 60% of knees. Preexisting cardiac disease was associated with a higher likelihood of failure to control infection in all treatment groups. Antibiotic-resistant Staphylococci continue to compromise treatment outcome of prosthetic joint infections, especially in patients with medical comorbidities. New preventive and therapeutic strategies are needed. Level of Evidence: Level IV, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.